MUHAMMADIYAH DAN TASAWUF: SUATU PRAKTIK DI SEKOLAH DASAR: ANALISIS INTERNALISASI NILAI SUFISME DALAM KURIKULUM SEKOLAH DASAR - Riza Awal Novanto; Moh. Nurhakim; Khozin (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2024)
This study explores the practice of Sufism within the educational context of SD Muhammadiyah Kademangaran, an institution under the auspices of the Muhammadiyah organization. Known for its modern and reformist approach to Islam, Muhammadiyah is often perceived as giving little room to the more mystical and introspective practices of Sufism. This case study employs a qualitative approach to deepen understanding of how elements of Sufism are integrated into the curriculum and daily school activities, and how these practices are received by teachers and students. Through in-depth interviews, participatory observations, and analysis of school documents, this research reveals that SD Muhammadiyah Kademangaran integrates Sufi values not only in the teaching of Islamic religion but also in the cultivation of student character and ethics. This practice demonstrates a harmonization between Muhammadiyah's rational approach and the spiritual aspects of Sufism, offering new insights into discussions on the diversity of religious practices in Islamic education in Indonesia. The study also highlights the challenges and opportunities in merging these seemingly opposing traditions, as well as the implications of such practices for the development of an inclusive and holistic Islamic education curriculum.